Relación del diámetro con altura total y comercial de un bosque de colina baja, distrito de Maquia, Loreto, 2023 - Caballero Ramirez, Galena Mabel (2024)
In the district of Maquia, Loreto, an evaluation of the relationship between diameter at breast height (DBH) and total and commercial height was carried out in a low hill forest. The information used came from the forest census of commercial species of operational plan 7 of the PC 6 cutting plot, designated for forestry use. The results reveal the presence of 81 different species, distributed in 25 botanical families and belonging to 69 genera. The tree density in the area was established at 1,005 trees per hectare, with a total of 728 trees registered in the study area. A significant relationship between diameter and total height stands out, evidenced by a correlation coefficient (r) of 0.595. Likewise, a similar relationship is observed between diameter and commercial height, with a correlation coefficient of 0.652. Both relationships are rated as moderate, indicating that as diameter at breast height increases, so do the total height and commercial height of the trees in this forest. These findings provide valuable information for the management and understanding of ecological processes in this specific forest region.